Integration Analysis of Activity Group for Decreasing of Stunting in Maluku - E. Tahitu, Meilvis; P. N. Damanik, Inta; Augustyn, G. H.; A. Ayhuan, Sherly; Nurjannah, Neima; Latuconsina, Hayati; Mardiman, Mardiman; Kuncoro, Desta Janu (Agrikan Jurnal Agribisnis Perikanan, 2023)
Stunting is a condition of growth failure of a child, both body and brain, therefore stunting must be prevented. Stunting prevention was carried out through various efforts, including activity groups (Poktan). This study aims to analyze the distribution of Poktan in Maluku and its problems and to analyze the integration of Poktan in reducing stunting. The research was conducted using secondary data sourced from Representative Office of BKKBN Maluku and various relevant literature sources as well as conducting formal and informal discussions with several staff from Representative BKKBN of Maluku and with research team from Pattimura University. The results showed that the distribution of Poktan in Maluku was evenly distributed in every region, but in terms of numbers it was still uneven. The problems faced by Poktan in Maluku include the lack of facilities and infrastructure of internet-based communication and transportation to support the implementation of Poktan functions, the number of assistants was still lacking, and the awareness of Poktan officers or assistants on the importance of data was still low. Poktan integration has taken place but needs to be improved so that it is better for supporting the reduction of stunting in Maluku. In addition, it requires cooperation between various parties from the government, the private sector, universities, the community, and various of mass media.